Les Difficultés D’apprentissage En Éducation Physique Et Sportive: Une Étude De Trois Cas D’enseignement De La Course De Haies Au Bénin - Basile, Agbodjogbe D.; Bachar M., Ogueboule; Kossivi, Attiklemé; Georges, Kpazaï (European Scientific Journal, ESJ, 2018)
This study explored the functioning of the in-situ didactic system to highlight the difficulties experienced by students in the third year of the secondary school level when performing the activities suggested by their Sport and Physical Education Teachers. Based on the logic of the ternarity of the didactic system (Amade-Escot, 2008; 2003), the interactions between the teachers and students during the teaching/learning of the race were the subjects of study. A triangulation method was utilized whereby data was collected by extracting information from various sources including (Leutenegger, 2009; Van Der Maren, 1996): documentary analysis, interviews conducted pre-session, post-session, and post-cycle, as well as audio-visual recording of the class sessions. Central concepts within the anthropological theory of didactic (Chevallard, 1992) and didactic joint action theory (Sensevy, 2007) were used to analyze and interpret the results of which the most salient revealed that the students have difficulty with crossing and resuming the race after the hurdle. The inter-hurdle race does not occur at regular intervals. These are difficulties previously noted by Lamote (2002) and Aubert (1994). Within the context of our investigation, the agglomeration of the contents of the program, the number of sessions (03) devoted to the teaching/learning cycle of this physical activity, the quality of the material used, and the personal interactions between the participants, were all factors shown to account for the difficulties experienced by the students.